KONTRIBUSI KH. ALI MUSTAFA YAQUB DALAM MENGKONTEKSTUALISASIKAN HADIS DI INDONESIA - Yusi Yuliandini; Hidayati Hidayai (DIRAYAH : Jurnal Ilmu Hadis, 2024)
Islam has regulated that in understanding science, especially religious knowledge, it requires the guidance of a teacher who has good credibility, especially in undrstanding the hadith spread in Indonesia. Because the power that the word "hadith" bear, leads to a number of people thinking that it must be obeyed or carried out absolutely without looking at the context of life in Indonesia. Even though in interpreting the hadith itself there are certain rules that must be fulfilled so that  they can be harmonious and not cause misunderstanding. In this research, the writer discusses about KH. Ali Mustafa Yaqub's way of understanding hadith contextually along with examples of hadiths. This research is library research using qualitative methods, which is research that contains descriptive data. The results of this research show that the contribution of KH. Ali Mustafa Yaqub's thoughts is very large for Islamic scholarship in Indonesia, one of which is in contextualizing hadith in Indonesia. Judging from his active participation in various institutions as well as his works in the field of hadith with brilliant ideas.